Illegal Fishing Nelayan Vietnam: Perspektif Keamanan Kawasan RI di Laut Natuna - Rifai, Maulana; Jatmoko, Rara Tiara Lestari (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
Illegal fishing conducted by Vietnamese fishermen presents a complex and multifaceted problem for Indonesia, particularly in the economic and environmental spheres, with direct consequences for the fisheries and marine sectors. This study aims to investigate the underlying causes of Vietnam’s persistent illegal fishing activities in the Northern Natuna Sea, a region rich in marine biodiversity and economic potential. The research applies a qualitative-descriptive method, utilizing secondary data sources such as news articles, academic journals, government publications, and other credible media. The analysis involves categorizing, examining, and interpreting the data to identify the main drivers behind Vietnam's illegal fishing behavior. One of the core findings highlights that the abundant natural marine resources in the Natuna Sea, which spans approximately 262,197.07 km², serve as a major incentive for Vietnamese fishers to exploit the area. Additionally, weak enforcement, overlapping territorial claims, and economic pressures in Vietnam contribute significantly to this transnational issue. The study also emphasizes the strategic role of the Indonesian government in strengthening maritime surveillance, law enforcement, and diplomatic engagement to curb these unlawful activities. Addressing this issue not only preserves Indonesia's sovereignty but also ensures sustainable marine resource management in the region. This research contributes to the broader discourse on maritime security and regional cooperation in Southeast Asia.